Homework in Macroeconomics: Household Production and Aggregate Fluctuations - Benhabib, Jess; Rogerson, Richard; Wright, Randall (Journal of Political Economy, 1991)
This paper explores some macroeconomic implications of including household production in an otherwise standard real business cycle model. The authors calibrate the model on the basis of microeconomic evidence and long-run considerations, simulate it, and examine its statistical properties. They find that introducing home production significantly improves the quantitative performance of the standard model along several dimensions. It also implies a very different interpretation of the nature of aggregate fluctuations. Copyright 1991 by University of Chicago Press.